Are Wage Cost Differentials Driving Delocalisation? - Jozef Konings (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
This paper compares the wage cost and productivity differentials between Belgium and Portugal, being the EU benchmarks for high and low labor costs, with those in the three leading emerging economies of Central and Eastern Europe, Poland, Hungary and the Czech Republic. To this end we use firm level data to construct measures of labor costs and labor productivity. We find that labor costs are more than 5 times larger in Belgium compared to Central and Eastern Europe. But also compared to Portugal, labor costs in Belgium are 4 times larger, indicating that even within the EU there are huge differences in labor costs. However, at the same time labor productivity varies substantially between these regions and there is a close correlation between high wage costs and high labor productivity. Third, we compute a competitiveness index (the ratio of wage costs to labor productivity) and find that by the year 2000, Poland is less competitive than the high income country, Belgium. Furthfirmore, we find that high labor cost relative to productivity sectors in Belgium are also high labor costs relative to productivity sectors in the other low wage regions, suggesting that the incentives to delocate production from high to low wage regions are not that straightforward. Finally, we estimate firm level labor demand in Belgian manufacturing. We find no evidence that labor costs in Central and Eastern Europe destroy jobs in Belgian firms on average. However, we have some support for the idea that the evolution of labor costs relative to productivity in Portugal has some depressing effect on jobs in Belgian firms, although that such an effect is estimated to be relatively low. The main conclusion of this paper is that on average there is no evidence that low wage competition from Central and Eastern Europe has a negative effect on jobs in Belgian manufacturing.
Keywords: 330; Arbeitskosten; Arbeitsproduktivität; Lohnniveau; Internationaler Wettbewerb; Belgien; Portugal; Polen; Tschechische Republik; Ungarn